(untitled) (Fiep Bulletin - online, 2017)
The present study has the object analyze Quality of Life (QOL) of docents who act in graduation in Production Engineering in the Brazilian South. For that, the instrument WHOQOL-bref was applied by Google Drive platform to 42 professors of Production Engineering inserted in programs of graduation in the Brazilian South. For the stage data analysis, it was used tool for calculating the scores and descriptive analysis about the instrument, available in Pedroso et al. (2010). The results emphasize the bigger lack in QOL of the respondents, about the facets, they were: Physical Environment (51.19), Sleep and rest (57.74) and Positive Feelings (59.52), but they contribute to justify the elevate scores at Home Environment (82.14) and Self-esteem (81.55). Thus, it allows to infer that the docent profession exerts negative and positive influences on the quality of life about this public.